Meatal stenosis posttraditional neonatal circumcision-cross-sectional study - Ammar Fadil Abid (Urology Annals, 2021)
Context: Circumcision holds a unique place in the daily practice of urology. Heat cautery device is the most common local technique used, we found it can cause meatal stenosis (MS) and its sequels. Aim: The study aims to determine the incidence, presenting symptoms of MS and its relation to local traditional neonatal circumcision techniques among our children. Settings and Design: This study was retrospectively study. Materials and Methods: A total of 150 children who circumcised during the infancy period, outside medical institutes, and they circumcised using local traditional techniques either heating cautery devices or surgical knives. Statistical Analysis: Of data were carried out using the Statistical Packages for the Social Sciences - version 25 (IBM Corporation). Results: Of 150 children, 60 (40%) had MS. The mean age at the time of diagnosis was 5.98 ± 3.06 years (range 1–13 years) and the majority of patients were within the age group of 5–9 years (n = 31, 51.7%), median 6.0 years. The incidence of MS was significantly higher (P = 0.037) among a group of children circumcised with a heating device in comparison with the circumcised group with other methods. Forty-six children (76.7%) were symptomatic and fourteen children (23.3%) diagnosis of MS had performed incidentally. Conclusions: MS is a long-term complication of neonatal circumcision with a late presentation and sequels. It is more common among group circumcised using heating cautery. We recommend using heating cautery cautiously.